2017
DOI: 10.3390/jmmp1020021
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Dual-Phase High Carbon Steel—Microstructure Influence

Abstract: Dual-phase high carbon steel is widely used in mining and in chemical industry applications in highly abrasive environments due to its excellent hardness and abrasion resistance. In recent years, the use of less expensive but more corrosive solutions in industrial processes has become more common. As a result, detailed understanding of the corrosion behaviour of dual-phase high carbon steel is needed; an issue that has, to date, been little-studied. This study investigates in detail the corrosion behaviour of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…With relatively smaller grain size of both phases on HCS-B and HCS-D on interface region, it has higher potential risk of corrosion attack than HCS-C. This aspect was due to higher boundary-to-boundary contact and the difference in potential energy between phases, thus, prone to boundary and pitting corrosion [14,15]. The other aspect was because of martensite has higher carbon (C) content than retained austenite that possessed higher iron (Fe) content, resulting martensitic phase acted as cathode, whereas the austenitic phase referred as anode, hence preferential attack on retained austenite [14,15].…”
Section: Synthesis Of Ceramic Layer Into Steel Substratementioning
confidence: 99%
See 1 more Smart Citation
“…With relatively smaller grain size of both phases on HCS-B and HCS-D on interface region, it has higher potential risk of corrosion attack than HCS-C. This aspect was due to higher boundary-to-boundary contact and the difference in potential energy between phases, thus, prone to boundary and pitting corrosion [14,15]. The other aspect was because of martensite has higher carbon (C) content than retained austenite that possessed higher iron (Fe) content, resulting martensitic phase acted as cathode, whereas the austenitic phase referred as anode, hence preferential attack on retained austenite [14,15].…”
Section: Synthesis Of Ceramic Layer Into Steel Substratementioning
confidence: 99%
“…This aspect was due to higher boundary-to-boundary contact and the difference in potential energy between phases, thus, prone to boundary and pitting corrosion [14,15]. The other aspect was because of martensite has higher carbon (C) content than retained austenite that possessed higher iron (Fe) content, resulting martensitic phase acted as cathode, whereas the austenitic phase referred as anode, hence preferential attack on retained austenite [14,15]. As results, bulk properties remained unmodified with layers being formed in three waste-treated samples through the reduction process of the wastes [16] into substrate of the steel.…”
Section: Synthesis Of Ceramic Layer Into Steel Substratementioning
confidence: 99%
“…However, the decrease in the hardness due to the corrosion attack was slightly different in all the samples. One of the reasons is due to less corrosion in the base material [9,10] compared to the other two samples because of the solid-state phase transformation that increased the dislocation density, plastic deformation and residual stress between the constituent phases. Another reason is that corrosion has a negative effect on surface mechanical properties, such as grain boundary corrosion between the interface of martensite and austenite phases, which weakens the overall integrity of each phase, thus reducing the surface hardness properties.…”
Section: Corrosion Rate Low>>moderate>>highmentioning
confidence: 99%
“…Recent studies by Handoko et al [9] on dual-phase high carbon steel revealed that a preferential attack on retained austenite was followed by martensite in the corrosion process. This phenomenon was due to the different carbon content in which the martensitic phase possessed a higher percentage as compared to the austenitic phase [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation